MicroRNA-548a-5p promotes proliferation and inhibits apoptosis in hepatocellular carcinoma cells by targeting Tg737 - Zhao, Ge (World J Gastroenterol, 2016)
AIM: To investigate whether Tg737 is regulated by microRNA-548a-5p (miR-548a-5p), and correlates with hepatocellular carcinoma (HCC) cell proliferation and apoptosis. METHODS: Assays of loss of function of Tg737 were performed by the colony formation assay, CCK assay and cell cycle assay in HCC cell lines. The interaction between miR-548a-5p and its downstream target, Tg737, was evaluated by a dual-luciferase reporter assay and quantitative real-time polymerase chain reaction. Tg737 was then up-regulated in HCC cells to evaluate its effect on miR-548a-5p regulation. HepG2 cells stably overexpressing miR-548a-5p or miR-control were also subcutaneously inoculated into nude mice to evaluate the effect of miR-548a-5p up-regulation on in vivo tumor growth. As the final step, the effect of miR-548a-5p on the apoptosis induced by cisplatin was evaluated by flow cytometry. RESULTS: Down-regulation of Tg737, which is a target gene of miR-548a-5p, accelerated HCC cell proliferation, and miR-548a-5p promoted HCC cell proliferation in vitro and in vivo. Like the down-regulation of Tg737, overexpression of miR-548a-5p in HCC cell lines promoted cell proliferation, increased colony forming ability and hampered cell apoptosis. In addition, miR-548a-5p overexpression increased HCC cell growth in vivo. MiR-548a-5p down-regulated Tg737 expression through direct contact with its 3’ untranslated region (UTR), and miR-548a-5p expression was negatively correlated with Tg737 levels in HCC specimens. Restoring Tg737 (without the 3’UTR) significantly hampered miR-548a-5p induced cell proliferation, and rescued the miR-548a-5p induced cell proliferation inhibition and apoptosis induced by cisplatin. CONCLUSION: MiR-548a-5p negatively regulates the tumor inhibitor gene Tg737 and promotes tumorigenesis in vitro and in vivo, indicating its potential as a novel therapeutic target for HCC.